Visual Pleasure In Pakistani Cinema (1947–2014) - Rizvi, Wajiha (Penerbit Universiti Sains Malaysia (USM Press), 2014)
The study discusses the evolution of Pakistani cinema as a gendered medium to analyse the changes in visual pleasure and the male and female gaze in regards to representations of real Pakistani women in films released for exhibition before and after the issuance of the Motion Picture Ordinance of 1979. It discusses how the élite gazing at the traditional, introvert chhooi-mooi girls, who never raised their eyes before the elderly and men and closely guarded their self-respect and sexuality in early films, differs from the lower classes gazing at free women who are open with their emotions and sexuality in contemporary films. The study uses the critical theories by Mulvey, Derrida, Rosen, and Comolli and Narboni to discuss male fascination and anxiety with the female form, social formations and epistemology to examine the difference between real women and their representation in films from both eras. For this purpose, it focuses on the chhooimooi girls of the black and white (B&W) cinema from Qaidi (The Prisoner) (1962) and Paristan (The Fairy Land) (1968), as opposed to modern exhibitionist "rain dancers" who reveal their bodies and join terrifying villains and vulgar comedians to make "the trio to get-real-culture" in the coloured Sher-e-Lahore (2001) and Choorrian (Bangles) (2001). The study finds that the attitude of the Central Board of Film Censors (CBFC) towards exhibiting films like Chingari (Vigor) (1964) and Sher-e-Lahore (2001) was puritanical earlier and progressive later. The images of real women and their representations mirror shifts in the opposite directions since Zia: the celebrities have become freer and open with their emotions as opposed to the celebrities of earlier films, while real women have become more conservative as opposed to the earlier women. This phenomenon signifies resistance to oppression by women and society in both the pre-and-post-Zia films